Novel L-type lectin from fresh water prawn, Macrobrachium rosenbergii participates in antibacterial and antiviral immune responses. Issue 77 (June 2018) - Huang, Xin; Han, Keke; Li, Tingting; Wang, Wen; Ren, Qian
Abstract: L-type lectins (LTLs) play important roles in the secretory pathway of animals, including selective protein trafficking, sorting, and targeting. They have a leguminous lectin domain and can bind to high-mannose-type oligosaccharides. In this study, a novel LTL, designated as MrVIP36, was identified from Macrobrachium rosenbergii . The full-length cDNA of MrVIP36 was 1687 bp with a 972 bp open reading frame encoding a putative protein of 323 deduced amino acids. The deduced MrVIP36 protein contained an LTL-like domain (LTLD) and a transmembrane domain. Phylogenetic tree analysis indicated that MrVIP36 was a member of invertebrate LTLs. It has a closer evolutionary distance with invertebrate LTLs than vertebrate LTLs. Quantitative real time polymerase chain reaction showed that MrVIP36 is expressed widely in all tested tissues, especially in the hepatopancreas and intestine. MrVIP36 was significantly up-regulated in hemocytes of prawns at different time points after Staphylococcus aureus, Vibrio parahaemolyticus, and White spot syndrome virus (WSSV) infections. The recombinant protein MrLTLD (rMrLTLD) could bind and agglutinate all tested bacteria. Sugar binding assay revealed that rMrLTLD could also bind to the glycoconjugates of the bacterial surface, such as lipopolysaccharide and peptidoglycan. Moreover, rMrLTLD could inhibit the growth activities of microorganisms in vitro and accelerate the bacterial clearance in vivo . rMrLTLD could also inhibit WSSV replication in vivo . Survival rate analysis showed that rMrLTLD could protect prawns against WSSV infection. Taken together, our results suggested that MrVIP36 functioned as a pattern recognition receptor involved in the antibacterial and antiviral immune responses of M. rosenbergii . Highlights: Novel L type lectin was identified from M. rosenbergii, named as MrVIP36. MrVIP36 was regulated by bacteria and virus. rMrLTLD could recognize glycoconjugates, bind and agglutinate various bacteria. rMrLTLD could inhibit the growth activities of microorganisms in vitro and accelerate the bacterial clearance in vivo. rMrLTLD could also inhibit the virus replication in vivo and then reduce the mortality of M. rosenbergii.